Individual or Structural Inequality? Access and Barriers in Welfare Services for Women Who Sell Sex - Brunovskis, Anette (2018)
It is often taken for granted that women who sell sex are vulnerable, that welfare services can and should alleviate this vulnerability, and as such, being defined as ‘vulnerable’ can be beneficial and associated with special rights that would otherwise be inaccessible. At the same time, ongoing debates have demonstrated that establishing individuals and groups as vulnerable tends to mask structural factors in inequality and has negative consequences, among them an idea that the path to ‘non-vulnerability’ lies in changing the ‘afflicted’ individuals or groups, not in structures or in addressing unequal access to resources. In this article, we take this as a starting point and discuss challenges for the welfare state in meeting the varied and often complex needs of sex sellers. Based on qualitative research with service providers in specialised social and health services in Norway, we examine access and barriers to services among female sex sellers as well as how vulnerability is u